Psychosocial Status of Hypertensive Teachers - Razzaq Jawad, Saeed; Jassim Mohammed, Hussein (International Journal of Psychosocial Rehabilitation, 2020)
The correlation between hypertension and the psychosocial state of teachers has become common due to the psychological and social pressures they are exposed to as a result of the teaching and psychological stress surrounding them. The study goals are to identify the psychosocial domain of teachers and find out the correlation between the psychosocial domain and hypertension of teachers. An appropriate sample of teachers was taken in the Al-Najaf Al-Ashraf city (n = 274) to conduct the research. Questionnaire tools were created by the researcher for collecting the study sample. The questionnaire validity was determined by a committee consisting of (14) experts distributed among (4) colleges. The tool reliability was detected by using the method test in the study that was conducted, and the questionnaire tools were used to collect samples, and its value was 0.824. The finding of the study confirmed that the majority of teachers are male (60.6%), and 84.7% of them live a civilian life and suffer from hypertension stage 1 (33.6%), and with a fair psychosocial level, there is a strong correlation (p = 0.00) between the hypertension and the psychosocial status. All teachers have a moderate cognitive (mean score = 2.023) and emotional (mean score = 1.932) level, and the majority of them have a moderate social-behavioral (mean score = 2.076) and general health (mean score = 2.386) level. I recommend cooperation between the Ministries of Health and Education for early detection of hypertensive teachers and increasing teachers’ knowledge about the impact of psychosocial status on hypertension.